2019
DOI: 10.1037/ser0000295
|View full text |Cite
|
Sign up to set email alerts
|

Raw-score equivalence of computer-assisted and paper versions of WISC–V.

Abstract: The adaptation of individually administered psychological tests from paper to app-based administration formats can present unique threats to the construct and raw-score equivalence of the paper and digital formats. We discuss these potential threats and describe a study evaluating the equivalence of paper and digital versions of the Wechsler Intelligence Scale for Children, fifth edition (WISC–V), which has been adapted to an app-based testing platform called Q-interactive. The present study (N = 350) used an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 15 publications
0
22
0
1
Order By: Relevance
“…Many studies have reported on the psychometric equivalence of administering tests via paper-and-pencil and computer formats using an in-person administration (e.g., Daniel & Wahlstrom, 2019;Daniel et al, 2014;Finger & Ones, 1999;Forbey & Ben-Porath, 2007;Menton et al, 2019;Pinsoneault, 1996;Roper et al, 1995). Fewer studies have focused on the comparison between in-person vs remote administration formats of psychological tests, particularly with respect to performance tasks (e.g., Brearly et al, 2017;Chuah et al, 2006;Marra et al, 2020;Wright, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have reported on the psychometric equivalence of administering tests via paper-and-pencil and computer formats using an in-person administration (e.g., Daniel & Wahlstrom, 2019;Daniel et al, 2014;Finger & Ones, 1999;Forbey & Ben-Porath, 2007;Menton et al, 2019;Pinsoneault, 1996;Roper et al, 1995). Fewer studies have focused on the comparison between in-person vs remote administration formats of psychological tests, particularly with respect to performance tasks (e.g., Brearly et al, 2017;Chuah et al, 2006;Marra et al, 2020;Wright, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Given that raw scores of the tablet-administered K-RBANS have limitations using the norm sample of paper-administered K-RBANS because it would be easily affected by age, education, and gender, raw scores would be more sensitive to the format effect. However, it needs to be refined carefully so that the equivalence of raw scores can reduce potential threats to the adaptation of psychological tests [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…Among the available studies directly assessing the equivalence of scores obtained from cognitive and achievement assessments through virtual and in-person formats among children and youth, the results generally suggested that the mode of administration did not impact examinees' performance on the tests (Daniel & Wahlstrom, 2019;Harder et al, 2020;Wright, 2018a). However, not all subtests showed equivalent scores across administration methods.…”
Section: Research On Tele-assessmentmentioning
confidence: 98%